EFEKTIVITAS PELAYANAN ONLINE MENGGUNAKAN LIVIN’ BY MANDIRI DI PT BANK MANDIRI AREA SUKABUMI - Alawiyah, Anissa; Fajar Basori, Yana; Purwanti, Dian (Prodi Administrasi Publik FISIP UNPAS, 2023)
Bank is an institution that becomes a place or place to carry out various transactions related to finance. By collecting funds from the public in the form of savings and channeling these funds back to the community in the form of loans. Along with the development of technology and information, there is an evolution that leads to digital banking services. This service aims to improve the effectiveness of the Bank's operational activities and service quality to the public in general and customers in particular. For this reason, PT Bank Mandiri Sukabumi Area as a State-Owned Enterprise (BUMN) follows the policies set by the head office regarding digital transaction services by presenting an online application called Livin 'By Mandiri. The online application is expected to be able to provide online services effectively in transactions, so that problems that often occur such as service limits at service hours, long and long queues and other problems that arise can be resolved by using online services using Livin 'By Mandiri. Various kinds of features are presented to make it easier for people to make transactions without having to waste time and energy going directly to the bank. The whole community can use Livin' By independently anywhere and anytime without any time limit. However, not all people immediately want to use the Livin 'By Mandiri online service policy, there are some customers who do not know or do not understand how to use the online service application. The type of research used is descriptive research using a qualitative approach. Continuous education is needed so that all people can enjoy the convenience of online transactions using Livin By Mandiri